In it together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Two major mergers have recently been concluded in international agricultural research. The International Board for Soil Research and Management (IBSRAM) and the International Water Management Institute (IWMI) now share headquarters at IWMI s...